Adenophoraphis, a new aphid genus from Kazakhstan (Hemiptera: Aphididae: Macrosiphini) - Kadyrbekov, R.Kh. (Fundamental and Experimental Biology, 2024)
Currently, 889 species of aphids from three families are known in Kazakhstan: Adelgidae (10 species), Phylloxeridae (2), Aphididae (877) [1]. A new to science genus of aphids Adenophoraphis gen. n. and a new species Adenophoraphis burabaica sp. n. described from Kazakhstan. The specimens of the new taxon were collected in Akmola Region of the northern Kazakhstan in 2002. The new genus belongs to the subtribe Macrosiphina of the tribe Macrosiphini (Aphidinae). It lives on Adenophora liliifolia (L.) A. DC, no ant attendance was observed. During the collection period, only apterous viviparous females were found. The specimens were collected in a deciduous forest, in the Kazakh uplands, on the Kokshetau Upland. The new genus belongs to the subtribe Macrosiphina of the tribe Macrosiphini of the subfamily Aphidinae. In addition to the new genus, the other members of Macrosiphina inhabiting Campanulaceae include Campanulaphis Kadyrbekov, 2016, Megouroleucon Miyazaki, 1971, Tshernovaia Holman et Szelegiewicz, 1964 and Uroleucon Mordvilko, 1914.